2020
DOI: 10.9734/ijtdh/2020/v41i2430420
|View full text |Cite
|
Sign up to set email alerts
|

Face Mask Utilization in the Era of COVID-19: Nigeria Experience

Abstract: Background: The use of face masks has been accepted and recommended globally as a tool for COVID-19 protection. The government of Nigeria made wearing of face masks compulsory in public places. However, no evidence has shown user compliance or knowledge. This study investigated the knowledge and utilization of face masks among the Nigerian population. Methods: This was a web-based cross-sectional survey conducted from July 2 to August 28, 2020, using a convenience sampling technique. This was in adherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
4
5
2
Order By: Relevance
“…It was also found that the rate of facemasks usage was more in the urban area compared with the rural areas;this is similar toprevious report of more facemask usage in the urban areas [9]. This difference in facemask usage between the rural and the urban residentscould be mostly due to the difference in the socioeconomic statusesof people in the urban and the rural areas.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…It was also found that the rate of facemasks usage was more in the urban area compared with the rural areas;this is similar toprevious report of more facemask usage in the urban areas [9]. This difference in facemask usage between the rural and the urban residentscould be mostly due to the difference in the socioeconomic statusesof people in the urban and the rural areas.…”
Section: Discussionsupporting
confidence: 81%
“…The highest rate of facemasks usage/adherence was observed amongst the adolescentsthan people in other age categories. This is in contrast with previous studies which found adults to use facemasks more than adolescents [9,23]. Access to COVID-19 information especially through the internet is more common among the adolescents; this may have played an important role in in uencing the facemasks usage among them [9].…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations